PERCEPTION OF TEACHERS ON THE IMPACT OF QUALITY LEARNING ENVIRONMENT ON ACADEMIC PERFORMANCE OF PUPILS IN AWKA SOUTH LOCAL GOVERNMENT EDUCATION ZONE - Mbachi, Roseline Anurika; Okonkwo, Ogechukwu Jane; Nweke, MaryAnn Chimezie; Anolue, Chineme Chinwe; Obasi, David Chinonyerem (Journal of Early Childhood and Primary Education, 2025)
The study investigated the perception of teachers on the impact of quality learning environment on academic performance of Awka South L.G.A of Anambra State. The study was guided with three (3) research questions and three (3) hypotheses. The research adopted the descriptive survey design. The population for the study comprised of 627 public primary school teachers (265 male and 362 female teachers) in Awka South L.G.A. 109 teachers (35 male 74 female) primary five teachers were randomly selected through Simple random sampling and purposive sampling. A Questionnaire titled “Impact of Quality Learning Environment on Academic Performance of Pupils Questionnaire” was used as instrument for data collection. The instrument was validated by three education experts. Reliability of the instrument was determined with Cronbach alpha. The reliability test yielded reliability coefficients of 0.89, 0.83 and 0.90 were obtained for each of the clusters respectively with an over-all co-efficient value of 0.87. Mean and standard deviation were used as data analysis instrument while t-test was used to test the hypothesis at .05 level of significance. Findings revealed that primary school teachers perceive that the nature of the physical infrastructure such as the classroom dilapidated buildings, lack of computer laboratory and nature of the school playground had impacts on pupils academic performances. It also reveal that quality social learning environment such as cordial relationship among teachers, cordial relationship between teachers & instructional materials and socialization of pupils through play has meaningful impacts of pupils academic performances. There is a significant mean difference in the perception of male and female teachers on impact of quality physical learning environment on academic performance of primary five pupils. However, there was not significance difference in the perception of male and female teachers on quality social learning and quality temporal learning environment on pupils academic performances. The study recommends among others that entire head teachers should pay more attention in renovations of dilapidated physical infrastructures and procurement of instructional materials in schools to maximize pupil’s activeness to lessons which should contribute to their academic performances.